PENGARUH KONSENTRASI ELEKTROLIT DAN WAKTU ANODISASI TERHADAP KETAHANAN AUS, KEKERASAN SERTA KETEBALAN LAPISAN OKSIDA PADUAN ALUMINIUM PADA MATERIAL PISTON - Sidharta, Bambang Wahyu (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2014)
Aluminum alloys used in the manufacture of automotive parts, such as piston, wherein the component is fast moving parts, which would have to meet certain physical and mechanical properties such as wear resistance and hardness. To improve the physical and mechanical properties such as wear resistance and hardness in aluminum alloy, then the anodizing process was chosen, because this process will increase the hardness and wear resistance of the metal. The increasing of hardness and wear of the aluminum alloy is due to the aluminum oxide layer formed on the anodizing process.The purpose of this study was to determine the effect of electrolyte concentration and time of anodizing process against hardness and wear resistance , as well as the thickness of the oxide film on aluminum alloy as the piston material.The process of anodizing of aluminum alloys performed at different electrolyte concentrations, i.e. 15, 20 and 25% vol. H2SO4 (sulfuric acid) with the addition of 6% wt. H2C2O4 (oxalic acid) at each concentration of sulfuric acid. The length of the anodizing time for each electrolyte concentration of 3, 5 and 7 minutes, while the electric voltage used is 24 volts.From this research, the best results obtained by anodizing using electrolyte 15% vol. H2SO4 + 6% wt. H2C2O4 for 7-minute process that increase the material hardness from 115 to 190 VHN; and the best specific wear ​​(Ws) 7.15 x 10-5 mm2/kg and the thickest oxide layer 83.81 μm.